درجة ممارسة المشرفين التربويين للعلاقات الإنسانية في مهامهم الإشرافية "دراسة ميدانية لآراء معلمي الحلقة الأولى من مرحلة التعليم الأساسي في محافظة القنيطرة" - المقطرن سوزان; الصغير إيفا معن (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
هدف البحث إلى التعرف على درجة ممارسة المشرفين التربويين للعلاقات الإنسانية في مهامهم الإشرافية, وتحديد أكثر القيم الإنسانية التي يحتاج المشرفون التربويون إلى ممارستها أثناء قيامهم بتلك المهام, ومعرفة فيما إذا كانت هناك فروق ذات دلالة إحصائية بين آراء المعلمين حول درجة ممارسة المشرفين التربويين للعلاقات الإنسانية في مهامهم الإشرافية تبعاً لمتغيرات(الجنس,المؤهل العلمي والتربوي, سنوات الخبرة في التعليم), ولتحقيق هذه الأهداف تم تصميم استبانة مؤلفة من(22) فقرةطبقت على عينة من (147)معلماً ومعلمة,((37 ذكور وَ ( 110) إناث, وذلك في مدارس محافظة القنيطرة وقد توصل البحث إلى نتائج عدة من أهمها : 1- إن درجة ممارسة المشرفين التربويين للعلاقات الإنسانية في مهامهم الإشرافية كانتمتوسطة, حيث بلغت (1.94). 2- إن أكثر القيم الإنسانية التي يحتاج المشرفون التربويون إلى ممارستها أثناء قيامهم بمهامهم الإشرافية كانت قيم (العدل, المرونة, الثناء, تبادل الآراء, التحفيز, الأخذ بالآراء) 3- لا توجد فروق ذات دلالة إحصائية عند مستوى دلالة (0.05) بين آراء المعلمين حول درجة ممارسة المشرفين التربويين للعلاقات الإنسانية في مهامهم الإشرافية تعزى لمتغيرات: الجنس, المؤهل العلمي والتربوي, سنوات الخبرة في التعليم. This research aimed to know the degree to which the educational supervisors practice human relations in their supervising duties, identify the human values most ​​needed to be practised by the supervisors during their supervising duties, and to know whether there are statistically significant differences between teachers viewpoints based on variables of (gender, scientific and educational qualification, years of experience in education). Therefore, we designed a questionnaire including (22) items, and distributed on a sample of (147) teachers, (37) males and (110) females, from al Qoneitra schools. The findings of the research were as follows: 1-The degree to which the educational supervisors practice human relations in their supervising duties was medium and equals (1.94). 2 - the human values most ​​needed to be practised by the supervisors during their supervising duties were (justice, flexibility, praise, exchange of opinions, motivation, heeding opinions) 3 - There were no statistically significant differences in the degree to which the educational supervisors practice human relations in their supervising duties from the point of view of teachers based on variables of (gender, scientific and educational qualification, years of experience in education).